PENGARUH ABSENSI SIDIK JARI DAN UANG MAKAN TERHADAP KINERJA GURU RUMPUN PAI DI MTS NEGERI 2 KOTA BENGKULU - Siti Halina (UIN Fatmawati Sukarno Bengkulu, 2018)
This research started from the problem of giving of food money which is paid based on the attendance of civil ser- vant in working day, hence giving of food money can only be done if recapitulation of civil servant attendance for one month. This study aims to (1) to determine whether there is a significant and positive influence of fingerprint attendance variable and money meal variable against teacher performance variable PAI in MTs Negeri 2 Kota Bengkulu. The research method used survey method, questionnaire data collection technique and documentation. Data analysis techniques used in this study is to use multiple linear regression analysis. Data were collected, processed and analyzed using SPSS version 16.0. The results showed that (1) From the partial test result (t test) shows the probability significance (sig) of 0.031 <0.05, meaning that the fingerprint attendance significantly influences the performance of the PAI teacher is accepted. (2) From the partial test shows the probability of significance (sig) of 0.000 <0.05, meaning that the influence of the meal significantly influence the performance of PAI teacher group is accepted (3) From the simultaneous test results (Test F) shows sig probability. Fchange is 0.000. Since the Fchange value is less than 0.05 (0.05), thus fingerprint and fingerprint attendance significantly influence the PAI teacher’s performance is acceptable. Based on the value of R2 (R Square), the value of 0.993 is equal to 93%, meaning that the effect of fingerprint attendance and teacher’s meal money on teacher performance of PAI family is high, and the rest 7% is influenced by other factors not examined.